Communication and Emotional Vocabulary; Relevance for Mental Health Among School-Age Youths - Rimehaug, Tormod; Kårstad, Silja Berg (Frontiers in Psychology, 2022)
BACKGROUND: The association between language and mental health may be connected to several aspects of language. Based on the known associations, emotional vocabulary could be an important contribution to mental health and act as a risk, protective or resilience factor for mental health in general. As a preliminary test of this hypothesis, an assessment of emotional vocabulary was constructed and used among youths in school age. Cross-sectional associations and prediction models with parent-reported mental health as outcome were examined for emotional vocabulary as well as general vocabulary, non-verbal problem solving and social communication, controlled for age, gender and subsamples. RESULTS: Emotional vocabulary, general vocabulary and nonverbal problem solving was directly associated with each other and similarly associated with age and gender. However, they were not significantly associated with social communication skills or mental health in the expected direction. Only social communication skills showed significant negative associations with behavioral mental health problems, suggesting these skills to be potential resources related to mental health. IMPLICATION: Future research should investigate whether behavioral problems may be prevented or improved by developing better social communication skills among community school-age youths. However, our results suggest that merely expanding emotional vocabulary is not likely to produce such effects unless this is integrated with improving social communication.